THE ROLE OF PHYSICAL ACTIVITY IN ISLAM AND ITS IMPACT ON HUMAN HEALTH (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article highlights the significance of physical activity in Islam as both a religious and health-promoting practice. Physical training is viewed as a form of worship and fulfillment of amanah—the responsibility for one’s body. Through examples from the life of Prophet Muhammad (peace be upon him), the importance of sports such as running, wrestling, archery, and swimming is emphasized. Islam gives sport a spiritual dimension, linking health care with the strengthening of faith and discipline. Activity aligns with the objectives of Sharia, including the preservation of life and health.